The influence of retiree health benefits on retirement patterns - James Marton; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 2010)
We estimate the effect of employer offers of retiree health benefits (RHBs) on the timing of retirement using a sample of Health and Retirement Study (HRS) men observed over a period of up to 12 years. We hypothesize that the effect of RHBs differs for workers of different ages - a hypothesis we can test now that the main HRS cohort has aged sufficiently. We apply three wellknown panel data estimators and find that, for men in their 50s, RHBs have little or no effect on retirement decisions; however, a substantial effect emerges for men in their early 60s. We use simulations to illustrate how RHBs alter retirement patterns.
Keywords: J26; I18; J32; 330; retirement; health insurance; employee benefits; panel data; Flexible Altersgrenze; Betriebliche Sozialleistungen; Krankenversicherung; USA